Impulsivity, inhibition, and internet addiction in medical students of North of Iran - Salehi, Mohammad; Abbaspour, Zeinab; Molana, Aliasghar; Shahini, Najmeh (Frontiers in Psychiatry, 2023)
Background: Internet addiction, a serious psychological disorder, has rapidly increased among students and caused substantial interpersonal impairments. On the other hand, some evidence has indicated that impulsivity is associated with addictive behaviors. Objectives: There are a few studies concerning the relationship between internet addiction and impulsivity in Iranian students. Therefore, this study aimed to evaluate the relationship between impulsivity and internet addiction in the medical students of Golestan University of Medical Sciences, Golestan, Iran, within 2020-2021. Methods: In a cross-sectional study, 260 medical students at Golestan University of Medical Sciences in 2021 completed demographic, Barratt Impulsiveness Scale, and Young questionnaires and participated in a go/no-go computer test. Based on Young test scores, the students were divided into three groups of normal users, at-risk users, and users requiring treatment and compared regarding impulsivity and inhibition ability. Data was analyzed using SPSS v 23. Results: The mean age of the participants was 24.16 years. The results showed a significant correlation between impulsivity and internet addiction (p=0.001), which was established in all contextual indicators. A significant correlation was also shown between impulsivity and internet addiction (r=0.602 and p=0.001), both in male and female student. However, restraint index was correlated with internet addiction only in females (r=0.187 and p=0.033). Conclusion: Based on these findings, impulsivity increases alongside the rising of the internet addiction severity and does not influence by gender.